Project on Human Development in Chicago Neighborhoods (PHDCN): Prenatal and Early Health, Wave 2, 1997-2000 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Prenatal and Early Health interview. This was adapted from the National Maternal and Infant Health Survey which was developed by the National Institutes of Health (NATIONAL MATERNAL AND INFANT HEALTH SURVEY, 1988 [ICPSR 9730]). It included questions regarding the mother's pregnancy and delivery of the subject, as well as questions regarding the subject's early health. It was administered to the subject's primary caregiver for Cohort 0.